(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A compact and lightweight version of the electrolyzer has been created. It can be installed and used on any passenger car. According to the test results of the Nexia car, an increase in engine power by 10.8%, a decrease in gasoline consumption by 34.3%, a decrease in the CO content in exhaust gases by 2.15 times and CH by 3.96 times was noted. As a result, by increasing the engine power, an increase in the service life by 15-20% is achieved, by reducing gasoline consumption, an economic effect of 2700,000 soums per car is achieved and environmental pollution is reduced by 2-3 times.